The Meaning of Romanticism in the Lyrics of "Albi Ya Albi" by Nancy Ajram: Semiotics of Ferdinand de Saussure - Nurdin, Muthmainnah; Haeruddin, Haeruddin; Baso, Yusring Sanusi; Ridwan, Muhammad; Walidin , Muhammad (Journal of Language and Literature Studies, 2026)
Song lyrics are a form of language expression that contains emotional and symbolic meaning so that it can represent the experience of romance in a complex way. In modern Arabic popular music, Nancy Ajram's song Albi Ya Albi features a romanticism that not only portrays love as a simple feeling, but also presents inner conflict, longing, emotional uncertainty, and the need for validation of feelings. Therefore, this study aims to analyze the form of signifiers and signifiers and explain the construction of the meaning of romanticism in the lyrics of the song using Ferdinand de Saussure's semiotic approach. This study uses a descriptive qualitative method with data sources in the form of lyrics of the song Albi Ya Albi in Arabic. Analysis techniques are carried out through repeated reading, marker identification, sign interpretation, grouping of romantic meanings, and structural analysis of the relationship between markers and signs. The results show that the meaning of romanticism in songs is built through five main patterns, namely inner conflict, emotional helplessness, gradual awareness of love, emotional continuity, and emotional validation. The findings suggest that romanticism in songs is represented as ambivalent, reflective, and relational emotional experiences in the context of modern Arab popular culture. This research contributes to the study of semiotics, the lyrical analysis of Arabic songs, and the study of romanticism in popular music by showing that Ferdinand de Saussure's semiotics is able to uncover the systematic construction of romantic meaning through the relationship between linguistic forms and emotional meanings.